Mechanisms for activating specialized juvenile prosecutions 'Analytical study' (Zien Journal of Social Sciences and Humanities, 2023)
The study's main question is whether the Gaza Strip has the necessary resources to set up a specialized prosecution for juvenile cases. To address this question, the study looks at the mechanisms that can be used to activate a specialized juvenile prosecution. The significance of studying this subject is to ensure that juvenile offenders have legal protection both during the preliminary investigation processes with him and during his trial. To accomplish the study's goals, it was divided into: a preliminary section in which we discussed how to define a juvenile and a Palestinian child, and a first section in which we discussed how to prosecute juveniles during the preliminary investigation and how to end it. We discussed the establishment of the Public Prosecution, its mandate, and the potential for assigning the juvenile prosecution in the second section. In the end, the researcher came to several conclusions, the most significant of which was that the Public Prosecution must, when carrying out its duties, take into account the special legal procedures that must be provided to juveniles during their investigation in accordance with the laws in effect in the Gaza Strip